Fast and efficient separation of oil/saltwater emulsions with anti-fouling ZnO microsphere/carbon nanotube membranes. (December 2019) - Saththasivam, Jayaprakash; Wubulikasimu, Yiming; Ogunbiyi, Oluwaseun; Liu, Zhaoyang
Graphical abstract: Red arrows shows the CNT linkages between ZnO microspheres Abstract: A large quantity of oily and saline wastewater produced from the oil spill and oil/gas production is posing severe ecological and environmental issues. Conventional techniques for oil removal, such as floating booms, hydrocyclones, and chemical dispersant are inefficient in removing emulsified oil and could generate secondary environmental pollution. In this paper, we report a novel approach for fast and efficient separation of oil/water emulsions in saline environments with a new flexible and hierarchically-structured inorganic membrane. This new membrane is constructed with micro/nanostructured ZnO microspheres and carbon nanotubes. The new membrane has proven experimentally to separate oil/ water emulsions in saline environments, with an oil rejection rate of over 99.5% and high water flux of 3844 L/(m 2 .h.bar) under low operating pressure, thanks to their hierarchical micro/nano-structures. The separation performances of the membranes were relatively constant after multiple cycles of reuse, which suggest its superior anti-oil-fouling property of this membrane, due to its excellent underwater oleophobicity. The carbon nanotubes function as an inorganic binder that binds ZnO microspheres together and hence gives this inorganic membrane mechanical flexibility. This study provides a simple and cost-effective solution for fast and efficient oil/water separation in saline environments.